ANALISIS KEHILANGAN TEKANAN PADA SISTEM RESIRKULASI AIR TERKENDALI UNTUK PEMBENIHAN IKAN - Luthfi Riady; Indra Setiawan, Budi; Saptomo, Satyanto Krido (PERTETA, 2025)
Conventional fish hatchery faces many challenges, such as extensive land use, excessive water use, environmental pollution, and a controlled maintenance system, making the fish hatchery process inefficient. The development of a Controlled Water Recirculation System (SRAT) can be a solution to overcome this problem. This study aims to obtain a water balance model and determine the amount of pressure loss that occurs in the SRAT piping network to improve the performance of SRAT by maintaining the uniformity of water discharge in each water tank in the SRAT. First, the average discharge was 2,134 L/min, with a uniformity of only 79%. After the intervention of the model, the uniformity value increased to 99% with an average of 1,269 L/min. It can be concluded that the built model can maintain the uniformity of water discharge in each tub contained in the SRAT.